Employment performance and institutions: new answers to an old question - Bruno Amable; Lilas Demmou; Donatella Gatti (Institute for the Study of Labor (IZA), 2007)
This paper provides new evidence on the linkages between a large array of institutional arrangements (on product, labour and financial markets) and employment performance. Our analysis includes unemployment, inactivity and jobless rates, thus allowing us to control for possible substitution effects across situations of non-employment and to check whether institutional rigidities affecting unemployment impact inactivity along the same line. To cope with common problems related to the inclusion of time-invariant institutional variables in fixed effects models, we present results of regressions based on three different estimators: PCSE, GLS and FEVD, the last one being a new procedure specifically designed to treat slowly changing variables. We build time series data to account for annual evolution of employment protection legislation (EPL), and use new data for unemployment insurance net replacement rates. Moreover, we check for interdependencies across product and labour markets legislation by investigating the marginal impact of selected institutional variables. Among other results, we find evidence of a positive effect of EPL on employment performance as well as of a substitutability relationship across product and labour markets regulation policies.
urn:nbn:de:101:1-20080402433
Keywords: 330; Beschäftigung; Arbeitslosigkeit; Regulierung; Arbeitsmarktflexibilisierung; Industriestaaten